2014
DOI: 10.1111/liv.12570
|View full text |Cite
|
Sign up to set email alerts
|

The pan‐caspase inhibitor Emricasan (IDN‐6556) decreases liver injury and fibrosis in a murine model of non‐alcoholic steatohepatitis

Abstract: Background & Aims Hepatocyte apoptosis, the hallmark of non‐alcoholic steatohepatitis (NASH) contributes to liver injury and fibrosis. Although, both the intrinsic and extrinsic apoptotic pathways are involved in the pathogenesis of NASH, the final common step of apoptosis is executed by a family of cysteine‐proteases termed caspases. Thus, our aim was to ascertain if administration of Emricasan, a pan‐caspase inhibitor, ameliorates liver injury and fibrosis in a murine model of NASH. Methods C57/BL6J‐mice wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
151
1
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 246 publications
(163 citation statements)
references
References 72 publications
6
151
1
5
Order By: Relevance
“…This information supports the use of free fatty acids to study lipotoxicity in vitro. We have learned that NASH is a very proapoptotic disease (44), and inhibition of apoptosis may well be therapeutic in this disease (137). Consistent with these observations, palmitate and stearate induce robust apoptosis in hepatocytes (75); saturated fatty acids are more toxic than unsaturated fatty acids, but even unsaturated fatty acids, such as oleate, sensitize hepatocytes to death receptor-mediated apoptosis (14,46).…”
Section: What Have We Learned About Hepatic Lipotoxicity?supporting
confidence: 57%
“…This information supports the use of free fatty acids to study lipotoxicity in vitro. We have learned that NASH is a very proapoptotic disease (44), and inhibition of apoptosis may well be therapeutic in this disease (137). Consistent with these observations, palmitate and stearate induce robust apoptosis in hepatocytes (75); saturated fatty acids are more toxic than unsaturated fatty acids, but even unsaturated fatty acids, such as oleate, sensitize hepatocytes to death receptor-mediated apoptosis (14,46).…”
Section: What Have We Learned About Hepatic Lipotoxicity?supporting
confidence: 57%
“…A study from Hepatitis C virus infected patients and in NASH using murine model showed the blockage of hepatocytes apoptosis through administration of Emricasan (IDN-6556), a pan-caspase inhibitor ameliorates liver injury and fibrosis [5,6]. Similar results were found with Cathepsin-B inhibitor R-3032, that attenuate lipotoxicity associated with cholestasis [7].…”
Section: Cessation Of Damage Sourcesupporting
confidence: 71%
“…Mice with genetic deletion of caspase 8 in hepatocytes exhibited attenuated liver injury, inflammation, and fibrosis following methionine/cholinedeficient (MCD) diet feeding (14). Caspase inhibitors have been shown to be protective in animal models of NASH (15,16). Necroptosis is programmed necrosis that incorporates features of both apoptosis and necrosis (17,18).…”
Section: Introductionmentioning
confidence: 99%